(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Among the valuable economic characteristics, the vegetation period in the newly created systems was from 114 to 116 days. According to the results of the research, the fiber yield of families was higher than that of the standard variety, from 35.0% to 36.8% in the standard variety, and from 35.2% to 40.0% in families, which was 0.2-3.2% higher than that of the standard. Wilt infection was observed on average 2.4% in standard varieties, and no hybrid generations were infected with wilt.